How do motivational text messages impact motivation to exercise? Implications for the design of activity trackers - Duro, Lígia; Campos, Pedro F.; Romão, Teresa; Karapanos, Evangelos (My University, 2019)
We study the motives of regular and non-regular exercisers' engagement with motivational text messages and the importance individuals attribute to visual presentation. A total of 160 individuals were surveyed (80 regular exercisers and 80 non-regular exercisers). We found regular exercisers use motivational text messages in order to encourage their exercise routine. Non-regular exercisers use motivational text messages mainly to try to boost their exercise motivation. Individuals, independent of their exercise profile, prefer to see motivational text messages presented in a mixed way, sometimes as text-only and sometimes embedded in a visual presentation. Participants reported that an aesthetically appealing visual presentation helps instill a positive feeling regarding the text, and the visual presentation was considered as important as the textual content. We conclude with a number of implications for the design of activity trackers.
Keywords: Exercise motivation; Motivational text messages